2007
DOI: 10.1099/vir.0.82200-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of pentapeptide-insertion scanning mutagenesis for functional mapping of the plum pox virus helper component proteinase suppressor of gene silencing

Abstract: Helper component proteinase (HC-Pro) of Plum pox virus is a multifunctional potyvirus protein that has been examined intensively. In addition to its involvement in aphid transmission, genome amplification and long-distance movement, it is also one of the better-studied plant virus suppressors of RNA silencing. The first systematic analysis using pentapeptide-insertion scanning mutagenesis of the silencing suppression function of a potyvirus HC-Pro is presented here. Sixty-three in-frame insertion mutants, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 48 publications
2
47
0
4
Order By: Relevance
“…HC-Pro forms dimers/multimers and is active in these forms (48,51,59). Schematically, the HC-Pro protein can be divided into three regions: an N-terminal region associated with aphid transmission, a C-terminal region associated with proteinase and RSS activity (62), and a central region implicated in many functions, including RSS activity (48). The central region contains several motifs that are highly conserved in all potyviruses, including the FRNK box at amino acid positions 179 to 182 in mature HC-Pro, which is associated with Zucchini yellow mosaic virus (ZYMV) symptom severity (18).…”
mentioning
confidence: 99%
“…HC-Pro forms dimers/multimers and is active in these forms (48,51,59). Schematically, the HC-Pro protein can be divided into three regions: an N-terminal region associated with aphid transmission, a C-terminal region associated with proteinase and RSS activity (62), and a central region implicated in many functions, including RSS activity (48). The central region contains several motifs that are highly conserved in all potyviruses, including the FRNK box at amino acid positions 179 to 182 in mature HC-Pro, which is associated with Zucchini yellow mosaic virus (ZYMV) symptom severity (18).…”
mentioning
confidence: 99%
“…Although the exact role of CPD in RSS activity remains to be defined, an intact CPD structure seems to be important. Many mutations that abolish RSS activity appear to disrupt the CPD structure (23,24). We identified a surface on the CPD that is conserved in Potyvirus, but not in other genera of Potyviridae that contain a homologous CPD.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to proteolysis, the CPD of potyvirus has been associated with RSS activity (23,24). Although the exact role of CPD in RSS activity remains to be defined, an intact CPD structure seems to be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequences of HC-Pros of SMV G2 and G5 differed at 13 of 457 positions. While some research has suggested the existence of functional domains within the HC-Pro protein with the central domain responsible for suppression of RNA silencing (Varrelmann et al, 2007), other research has not supported that hypothesis (TorresBarceló et al, 2008;Wu et al, 2010). Hence, it was not possible to predict the effects of the individual amino acid sequence differences on suppression of RNA silencing from their positions alone.…”
Section: Methodsmentioning
confidence: 89%